Development of a functional prebiotic strawberry preparation by in situ enzymatic conversion of sucrose into fructo-oligosaccharides - Gonçalves, Daniela Alexandra (2023)
Food industry has been pressed to develop products with reduced sugar and low caloric value, while maintaining unchanged their rheological and physicochemical properties. The development of a strawberry preparation for the dairy industry, with prebiotic functionality, was herein investigated by in situ conversion of its intrinsic sucrose content into prebiotic fructo-oligosaccharides (FOS). Two commercial enzymatic complexes, Viscozyme® L and Pectinex® Ultra SP-L, were evaluated for the synthesis of FOS. Operational parameters such as temperature, pH, and enzyme:substrate ratio (E:S) were optimized to maximize FOS yield. The rheological and physicochemical properties of the obtained strawberry preparation were evaluated. For functional analysis, the resistance of FOS to the harsh conditions of the gastro-intestinal digestion was evaluated by applying the standardized INFOGEST static protocol. At optimal conditions (60 , pH 5.0), Pectinex® produced 265±3 g·L1 FOS, yielding 0.57±0.01 gFOS·gin.GF1 after 7hours reaction (E:S:1:40); and Viscozyme® produced 295±1 g·L1 FOS, yielding 0.66±0.00 gFOS·gin.GF1 after 5 hours (E:S:1:30). The obtained strawberry preparations contained more than 50%(w/w) prebiotic FOS incorporated (DP 35), with 80 % reduction of its sucrose content. The caloric value was therefore reduced by 2631%. FOS showed resistance to gastrointestinal digestion being only slightly hydrolysed (< 10%). Fructo-furanosylnystose was not digested at any phase of the digestion. Although the physicochemical properties of the prebiotic preparations were different from the original one, parameters such as the lower °Brix, water activity, consistency and viscosity, and its different color, may be easily adjusted. Results indicate that in situ synthesis strategies are efficient alternatives in the manufacture of reduced sugar and low-caloric food products with prebiotic potential.